Shape Memory Effect Driven by Diffusionless and Diffusional Transformations at Elevated Temperatures - Firstov, G.S.; Koval, Yu.N.; Van Humbeeck, J. (Успехи физики металлов, 2002)
Several alloy systems can be selected for high-temperature shape-memory alloys, defined as alloys with stable reverse martensitic-transformation temperatures above 100°C. However, due to the lack of minimum quality standards for stability, ductility, functional behaviour, and reliability, no successful applications have been realised so far. Nevertheless, research on high-temperature shape-memory alloys (HTSMA) is an important topic not only for scientific reasons but also due to the market pull. This paper reviews some novel HTSMA systems showing shape-memory effect at elevated temperatures driven by martensitic (diffusionless) and diffusional transformations